Performance Evaluation of BUMN Perkebunan After Restructuring - Dian Andrayani; Marimin Marimin; Sahara Sahara (School of Business, Bogor Agricultural University (SB-IPB), 2019)
SOE’s (BUMN) restructuring is one of the government's efforts to improve the performance and competitiveness of companies. However, this doesn’t necessarily occur due to differences in the challenges of change in each SOE. Therefore, to understand the impact of restructuring research on the performance evaluation of BUMN Perkebunan is needed. Data collection was carried out in May-November 2017 at Holding Perkebunan Office, Jakarta. The data used is secondary data in the form of company financial statements for the period 2012-2016. The data was processed by EVA methods to determine the economic value added to the company. The results showed that the highest and the only positive EVA was achieved before the restructuring, namely in 2012. After that, the EVA continued to decline and was at its lowest point in the third year after restructuring, namely in 2016. This decrease occurred due to the influence of components that support EVA, such as corporate income and expenditure, beta (ß), return market (rm), risk-free (rf), and the capital structure. To increase the EVA, the company has to make improvements by increasing the income, reducing the expenditure, reviewing the interest rate (rf), and keeping the proportion of capital structure.Keywords: Restructuring, BUMN Perkebunan, Performance Evaluation, EVA